Statelessness of an ethnic minority: the case of Rohingya - Bhattacharjee, Mowsume (Frontiers in Political Science, 2024)
This paper examines why and how Myanmar makes Rohingyas a stateless community in Southeast Asia, known as one of the most vulnerable human groups in the contemporary world. Based on the secondary evidence, the paper argues that Rohingyas are stateless because they are the victim of four discourses: former Bangladeshi people who illegally entered Myanmar; collaborators to British armies while Myanmar was fighting for its independence from British rule; attachment to Islamic terrorism; and foreign interests in the Rakhine state. The paper draws on a wide range of local and global literature to support its arguments. The paper uses extant sociological approaches to understand why a minority community becomes stateless and experiences genocide in their own country. The researcher developed an analytical framework to answer the research questions. This analytical framework draws on existing literature, recent strategies, theoretical understandings, contemporary data, and government responses to understand the process of Rohingya statelessness. This paper finds that Myanmar not only expelled Rohingyas from their homeland by imposing the blame on them but is also unwilling to return over a million Rohingyas from Bangladesh—a host country for them. The paper also finds that the international community is least concerned about the genocide and expulsion of the Rohingyas because of Myanmar’s communal agenda and foreign countries’ economic interests in the Rakhine state. The paper offers some recommendations to address this unique inhuman condition in its concluding part.